Public relations and code-switching: how technology shapes how we tell stories - Tombleson, Bridget; Wolf, Katharina (2019)
A storytelling ability has always sat at the core of professional communication skills and yet there has been little understanding as to why communication professionals are best placed to be the storytellers in an organisation. While many theories point to an understanding of audience, stakeholders and the media, as well as writing skill, a more primal occurrence is happening at a linguistic level as public relations practitioners become experts at code-switching their narratives according to the audience and platform used for communicating. Within the field of linguistics, code-switching is a process where a speaker mixes “two or more languages in discourse” (Poplack, 2001, p.2026) and as a part of this, a relationship is assumed between the language and social environment. A code-switching approach to storytelling allows public relations practitioners to meet audiences with a voice that is relevant, and open to participatory conversation. This is a form of adaptation for public relations practitioners, as they come to terms with the dynamics of modern storytelling in the digital age. This process while complex at times, is seemingly automatic for some, and has not been fully discussed as a key skill for 21st-century practitioners. Recently, the understanding of code-switching has been expanded to include changes in voice and use of vernacular depending on who the speaker is addressing. This is also relevant in visual communication in terms of understanding how the viewer decodes the image and changes the image to suit the audience. Previously thought to be exclusive to bilinguals, a form of code-switching can be used as a terminology for the process public relations professionals are undertaking when telling narratives across different platforms. Professional practitioners are often versed with a seemingly automatic understanding of different tone, audience and voice they must use across different platforms and it is this process that is a form of code-switching is happening as the narrative is ‘translated’ into the current ‘tribes’ voice. Code-switching theory, in particular, MacSwan’s (2010) constraint-free approach to analysing code-switching, can be used to explain how public relations practitioners communicate to different audiences and platforms and adjust tone and style. This critical reflection seeks to understand the process public relations practitioners are undertaking and look at examples to highlight the theory. Code-switching is a skill that is becoming more desirable as platforms and audiences fragment and become more personalised, and communication becomes more digital.